2011
DOI: 10.1161/atvbaha.110.219287
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Sesamol Derivative Inhibits Progression of Atherosclerosis

Abstract: Objective Sesamol, a phenolic component of lignans, has been previously shown to reduce lipopolysaccharide-induced oxidative stress and upregulate phosphatidylinositol 3-kinase/Akt/endothelial nitric oxide synthase pathways. In the present study, we synthesized a modified form of sesamol (INV-403) to enhance its properties and assessed its effects on atherosclerosis. Methods and Results Watanabe heritable hyperlipidemic rabbits were fed with high-cholesterol chow for 6 weeks and then randomized to receive hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…We previously showed that INV-403 had no LDL-lowering effects in LDLR-deficient WHHL rabbits ( 15 ). Consistent with this data, our current study, while demonstrating an effect of LDL lowering in wild-type mice, was unable to discern an effect on LDL lowering in LDLR Ϫ / Ϫ mice, indicating that LDLR may be essential for the LDL-lowering action of INV-403.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We previously showed that INV-403 had no LDL-lowering effects in LDLR-deficient WHHL rabbits ( 15 ). Consistent with this data, our current study, while demonstrating an effect of LDL lowering in wild-type mice, was unable to discern an effect on LDL lowering in LDLR Ϫ / Ϫ mice, indicating that LDLR may be essential for the LDL-lowering action of INV-403.…”
Section: Discussionsupporting
confidence: 87%
“…Target proteins were detected by primary antibodies as follows: mouse anti-␤ -actin LDLR ( 14 ). We previously synthesized an analog of methylenedioxyphenol (MDP), INV-403, and we demonstrated that, in a model of LDLR defi ciency, this small molecule inhibited atherosclerosis, paralleled by a decrease in aortic infl ammation oxidative stress and improvement in endothelial function without overt change in plasma lipid profi le and LDL ( 15 ). In the present study, we assess the effects of INV-403 and related analogs on cholesterol metabolism and LDLR expression, and we show that treatment with INV-403 unexpectedly and dramatically reduced plasma LDL, paralleled by an increase in the hepatic LDLR.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Similarly, MMP-13, -3, -1 and -9 are significantly higher in synovial fluids and serum of arthritic patients [3]. The MMP-mediated fibronectin degradative products are found to amplify cartilage degeneration, as they in turn activate MMPs and other inflammatory signals [7,29]. Thus, inhibition of HAase and MMPs is considered as a prime target to prevent disease perpetuation.…”
Section: Discussionmentioning
confidence: 99%
“…Sesamol (3, 4-methylenedioxyphenol) is one of the known phenolic antioxidant found in the sesame seed and has been shown to possess cardio-protective, hepato-protective, chemopreventive, anti-inflammatory, anti-diabetic, anti-atherogenic, and anti-aging properties. Lately, sesamol has been demonstrated to quench oxidative-nitrosative stress and inflammation by inhibiting NF-jB and IjB kinase (IKK) activation pathways [6,7]. Since arthritis is associated with secondary complications such as cardiovascular disorders and diabetes [8], it would be interesting to have a molecule that can prevent arthritis as well as oxidative stress-induced pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous inflammatory mediators, cell adhesion molecules, and cytokines were regulated by NFκB [20,21]. Thus, its activation has been considered as a hallmark of inflammation and was considered as a therapeutic target for atherosclerosis [22] and aortic aneurysm [23]. In our study, the heterodimers of p65/ p50 were activated and IL-6 and MCP-1 expressions were upregulated substantially.…”
Section: Discussionmentioning
confidence: 52%